Ku cyfrowym metamorfozom. Tradycja antyczna w cyberprzestrzeni - Aleksander W. Mikołajczak; Marek Kaźmierczak (Przestrzenie Teorii)
There are a lot of the dynamic meanings - important messages for the west civilization - in the antique tradition, deeply rooted in every medium. The authors of this text are showing us a lot of problems, connected with the ontological statue of text, context and relations among (not only between) sender and receiver, during the creating antique meanings in the different kinds of the communication. To be able to describe contemporary metamorphosis of the antique tradition they (the authors) are presenting us the most important changes in the west cultural reading - „through" the Internet - the antique heritage.